Shackling Persons with Mental Disability in International Human Rights Law and its Implementation in Indonesia - M Yakub Aiyub Kadir; Dara Rizki Fadillah (Faculty of Law Universitas Lampung, 2023)
This article investigates the implementation of human rights protection for persons with a mental disability who are being shackled and its challenges in Indonesia. Using a doctrinal and empirical approach, this article found that laws and regulations concerning persons with mental disabilities are yet not fully in line with international human rights law, and governments’ efforts to free persons with mental disabilities from shackling eventually have succeeded in reducing the number of shackling cases, however, have not been fully effective. Other obstacles in their community and family, such as stigma, discrimination, and lack of public knowledge about mental health, can hinder fulfilling the rights of persons with mental disabilities. It is recommended to revise articles or laws and regulations which infringe international law and scale up efforts, whether in funds allocation or human resources, facilities, and access to affordable, adequate rights-based mental health services.